Energy and exergy analysis of intensified condensate stabilization unit with water draw pan. (5th June 2019) - Tavan, Yadollah; Hosseini, Seyyed Hossein; Ahmadi, Goodarz
Graphical abstract: Highlights: The efficiency of water draw pan is investigated for industrial condensate stabilizer column. It is seen that most of free water accumulates at 2nd tray from top of the stabilizer column. Providing water draw off tray results in free water recovery up to 83%. Water draw pan significantly reduces reboiler and compressor duty in contrast with the no water draw pan condition. Higher exergy efficiency and uniform distribution of driving force is seen for the improved process. Abstract: An industrial condensate stabilizer unit is simulated with HYSYS 3.1 software when the excessive water is present on the trays. Effects of reboiler temperature, excess water flow rate, and incoming stream temperature on the Reid vapor pressure (RVP), temperature distribution along the column and impurity concentrations along the stabilization column, as well as, energy usage are studied. In addition, the optimal location for the water draw tray for the condensate stabilizer column is found. It is observed that the presence of water draw pan in the column leads to about 15% and 28% reduction, respectively, in the reboiler and the compressor duties compared to the industrial case without water draw pan. For the optimal case, 73% of excess water is recovered from the water draw pan. The presence of the water draw pan in the column also results in lower amount of impurities and higher heating value in the off-gas stream. Finally, the column with the water draw pan shows higher exergy efficiency of about 81% in comparison with the column without water draw pan (with exergy efficiency of about 72%).